Assessment of sexual dysfunction and its related factors in pregnant women referred to Mashhad health centers (2017-2018) - Salmeh Dadgar; Fatemeh Zahra Karimi; Mohadese Bakhshi; Mahbubeh Abdollahi; Fatemeh Rahimzadeh Borj (Mashhad University of Medical Sciences, 2018)
Introduction: Pregnancy is a phenomenon which is associated with very important physical and psychological changes. It plays an important role in women's sexual function, as sexual relationships are changing due to various physical and psychological changes during pregnancy. This study was performed with aim to evaluate sexual dysfunction and its related factors in pregnant women referred to Mashhad health centers. Methods: This cross-sectional study was conducted on 241 pregnant women referred to Mashhad health center in 2017. Data collection tools were demographic questionnaire and female sexual function Index. Data analysis was performed by SPSS software (version 16) and multi liner regression model test. P<0.05 was considered statistically significant. Results: The mean of total score of women's sexual performance was 26.47 ± 5.64 and 131 women (54.4%) had sexual dysfunction. Mean scores of sexual desire was 3.95 ± 0.98, Arousal 4.15 ± 1.19, Lubrication 4.64 ± 1.25, orgasm 3.53 ± 1.34, sexual satisfaction 4.89 ± 1.10 and painful intercourse 4.31 ± 1.36, and the most common sexual dysfunction were decreased sexual desire (46.5%) and Arousal (43.6%). The results of linear regression showed that previous history of delivery was related to sexual function, so that in the case of previous delivery, the mean of total score of sexual function decreased 1.86 unit (P = 0.01). Conclusion: Sexual dysfunction has high prevalence in pregnant women and history of previous delivery had a negative effect on sexual function. Therefore, it is suggested that sexual counseling programs be merged in prenatal care to improve the quality of pregnant women's care, and sexual counseling programs be designed and implemented especially for multiparous pregnant women.